Sistema informático de seguimiento, evaluación y control de trabajos de investigación de Uniandes Tulcán. - Villacorte Rivadeneira, Kevin David (2016)
In recent days the management and information system for monitoring, evaluating control research has presented a challenge in accepting and way of working for teachers and students, who are the main processes will interpret the use of new technologies education, since they face a model of traditional paper-based information management and managing virtual or multimedia tools as an alternative advertising, lack adequate to cope with this demand for new trends in education technology tools. That is why the interpret that have been mentioned above, have been working an finding how to cope with these shoricomings and have found altenative solutions. Such ls the use of computer monitoring, evaluation and control of research, which are not only made to improve the flow of information, monitoring and evaluation of research if that also meent to strangihen the knowledge of the research conducted at the institution. The correlation between the variables Monitoring, evaluation and control of research and lts various components scientists, is one of the actions under overcome these shoricomings have had to make finding a happy medium to respond, in the best way, to the needs facing. The results achieved when implementing a computer system that allows, strengthen monitoring, evaluation and control of research of Uniandes Tulcán have improved academic and research processes developed in this Institution.